KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE - Yulia Rahmah Anggraeni (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to (1) find out the activities of teachers and students during the implementation of mathematics learning activities by applying Think Pair Share (TPS) learning model, (2) knowing the improvement of students' mathematical communication skills on geometry. Based on the results of observations made by researchers, the cooperative learning model of the Think Pair Share (TPS) type has been going well. Teacher activities and student activities are in a good category, this can be seen from the average score of teacher activity in the first cycle reached 20.75 (good), in the second cycle to 23.25 (good). While the average observation score of students in the first cycle reached 13.75 (enough), in the second cycle it increased to 19.5 (good). The results of the communication skills test in the first cycle were in the adequate category (55.56% of 36 students) and in the next cycle increased to a good category (72.22% of 36 students). From the results of the tests in the second cycle, the study was stopped because it had reached the expected criteria, namely the number of students in good category â‰¥ 70% of 36 students. Thus it can be concluded that the application of the cooperative learning model of the Think Pair Share (TPS) type can improve the mathematical communication skills of students in class X MIPA 1 of SMAN 7 Bengkulu City.Keywords : Think Pair Share Learning Model, Mathematical Communication Ability